2013
DOI: 10.1111/jlme.12002
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Global NCD Crisis: Innovations in Law and Governance

Abstract: 35 million people die annually of non‐communicable diseases (NCDs), 80% of them in low‐ and middle‐income countries — representing a marked epidemiological transition from infectious to chronic diseases and from richer to poorer countries. The total number of NCDs is projected to rise by 17% over the coming decade, absent significant interventions. The NCD epidemic poses unique governance challenges: the causes are multifactorial, the affected populations diffuse, and effective responses require sustained mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…However, policy approaches within LICs depend upon a functioning governance system (Thomas and Gostin, ), which requires the necessary administrative resources and authority to implement health policies and regulations. LICs often lack these basic capacities, making it difficult for them to meet basic public health needs (Mok, , pp.…”
Section: Improving Affordabilitymentioning
confidence: 99%
“…However, policy approaches within LICs depend upon a functioning governance system (Thomas and Gostin, ), which requires the necessary administrative resources and authority to implement health policies and regulations. LICs often lack these basic capacities, making it difficult for them to meet basic public health needs (Mok, , pp.…”
Section: Improving Affordabilitymentioning
confidence: 99%
“…In order to accelerate the implementation of policies that improve the healthiness of food environments, a broader set of indicators adapted to the Mexican and Latin‐American context, focusing on public and private sector policies, was needed . The aim of this paper was to evaluate the current efforts of the Mexican Government towards creating healthier food environments, using the Food‐EPI tool and process.…”
Section: Introductionmentioning
confidence: 99%
“…The global economic burden of diet‐ and lifestyle‐related chronic diseases such as diabetes and cardiovascular diseases is estimated at $47 trillion from 2010 to 2030 (75% of global GDP in 2010, U.S. $63 trillion) while causing 60% of deaths globally; 80% of these deaths currently occur in low‐ and middle‐income countries, and this percentage is expected to increase rapidly . It has been suggested that this incredible economic and health burden of obesity and NCDs is the unexpected but natural outcome of ignoring nutrition and health in the many sectors of industrial innovation that shape lifestyle and environment, ranging from agriculture and food to transportation, housing, and communication technologies . The impact of rising obesity, for instance, on health care has been clearly demonstrated, and it is still increasing …”
Section: Introductionmentioning
confidence: 99%